Heart rate recovery and blood pressure response during exercise testing in patients with microvascular angina - Bong-Joon Kim; Eun-Ah Jo; Sung-Il Im; Hyun-Su Kim; Jung Ho Heo; Kyoung-Im Cho (BMC, 2019)
Abstract Background Angina pectoris with a normal coronary angiogram, termed microvascular angina (MVA), is an important clinical entity; however, its causes remain unclear. Autonomic dysfunction is one of the possible causes. Therefore, this study aimed to investigate parasympathetic dysfunction assessed by heart rate recovery (HRR) and increased sympathetic activity assessed by exaggerated blood pressure (BP) response (EBPR) to exercise in MVA. Methods The study participants were consecutive patients with anginal chest pain who underwent both coronary angiography with an ergonovine provocation test and a treadmill exercise test between January 2008 and February 2015. Patients with significant coronary artery disease (coronary artery stenosis ≥50%) or significant coronary artery spasm (≥90%) were excluded. Based on the treadmill exercise test, patients were categorized into the microvascular angina (MVA) group (patients with uniform ST depression ≥1 mm) and the control group. HRR was defined as peak heart rate minus heart rate after a 1 min recovery; blunted HRR was defined as ≤12 beats/min. EBPR was defined as a peak exercise systolic BP ≥210 mmHg in men and ≥ 190 mmHg in women. These parameters were compared between patients with MVA and the controls. Results Among the 970 enrolled patients (mean age 53.1 years; female 59.0%), 191 (20.0%) were diagnosed with MVA. In baseline characteristics, the MVA group had older participants, female predominance, and a higher prevalence of hypertension. The MVA group showed significantly lower HRR 1 min (24.9 ± 15.9 vs. 31.3 ± 22.7, p <  0.001) compared with the control group. Moreover, the proportion of EBPR was significantly higher in the MVA group than in the control group (21.5% vs. 11.6%, p <  0.001). Multivariable logistic regression analysis showed that age (odds ratio (OR), 1.045; 95% confidence interval (CI), 1.026-1.064; p <  0.001), HRR 1 min (OR, 0.990; 95% CI, 0.982-0.999; p = 0.022), and EBPR (OR, 1.657; 95% CI, 1.074-2.554; p = 0.022) were independently associated with MVA. Conclusion HRR and EBPR were associated with MVA, which suggests a link between MVA and autonomic dysregulation.